A scientific research topic trend prediction model based on multi‐LSTM and graph convolutional network. Issue 9 (9th February 2022) - Xu, Mingying; Du, Junping; Xue, Zhe; Guan, Zeli; Kou, Feifei; Shi, Lei
Abstract: Predicting the development trend of future scientific research not only provides a reference for researchers to understand the development of the discipline, but also provides support for decision‐making and fund allocation for decision‐makers. The continuous growth of scientific publications has brought challenges to track the development trends of scientific research topics. The existing topic trend prediction methods have proved that the research topic trend of a publication is influenced by other peer publications. However, they ignore the fact that the research topics of different publications belong to different research topic space. Moreover, the existing topic prediction methods do not fully consider the interactive influence among publications that the research topic of one publication affects the topics of other publications, it is also influenced by the research topics of other publications. In line with this, this paper proposes a scientific research topic trend prediction model based on multi‐long short‐term memory (multi‐LSTM) and Graph Convolutional Network. Specifically, multiple LSTMs are employed to map research topics of different publications into their respective topic space. Then, the graph convolutional neural network is applied to learn the scientific influence context of each publication, so that the research topic of each publication not only integrates the influence of neighbor nodes, but also considers the influence of the neighbors of the neighbor node on the research topic of the publication, so as to more accurately fuse scientific influence context of research topic of peer publications. Experiments results on the data set of scientific research papers in the field of artificial intelligence and data mining demonstrate that the model improves the prediction precision and achieves the state‐of‐the‐art research topic trend prediction effect compared with the other baseline models.